2014
DOI: 10.1007/s00417-014-2776-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wavelight Allegretto Eye-Q and Schwind Amaris 750S excimer laser in treatment of high astigmatism

Abstract: Purpose To compare functional outcomes of Wavelight Allegretto Eye-Q 400Hz and Schwind Amaris 750S excimer laser for astigmatism between 2 and 7 diopters(D). Methods Prospective comparative non-randomized case series of 480 eyes assigned in two laser groups and further divided into myopic and mixed astigmatism subgroups. All treatments were centered on corneal vertex. One-year results were compared between the groups. Statistical analysis was performed using z-test. Results Both Allegretto and Amaris postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Data from a review of recent studies of corneal laser refractive surgery for moderate to high astigmatism are given in Table E (available in the online version of this article). [4][5][6][8][9][10][11][12][13][14][15][16] Across these studies, the percentage of eyes achieving postoperative residual cylinder of 1.00 D or less after treatment for myopic astigmatism ranged from 39.6% to 95.7%, compared with 97.4% in our series. The percentage of eyes achieving a postopera- Topography-Guided Transepithelial Surface Ablation/Chen et al tive spherical equivalent within 1.00 D of the intended correction ranged from 86% to 99.2% compared with 99.3% in this study.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Data from a review of recent studies of corneal laser refractive surgery for moderate to high astigmatism are given in Table E (available in the online version of this article). [4][5][6][8][9][10][11][12][13][14][15][16] Across these studies, the percentage of eyes achieving postoperative residual cylinder of 1.00 D or less after treatment for myopic astigmatism ranged from 39.6% to 95.7%, compared with 97.4% in our series. The percentage of eyes achieving a postopera- Topography-Guided Transepithelial Surface Ablation/Chen et al tive spherical equivalent within 1.00 D of the intended correction ranged from 86% to 99.2% compared with 99.3% in this study.…”
Section: Discussionmentioning
confidence: 45%
“…Hyperopic and mixed astigmatism are technically demanding and difficult to correct. 13,14 We observed a slight undercorrection of astigmatism in both of our groups, but this was more evident in the mixed astigmatism group. Data indicating undercorrection of 4% (myopic astigmatism) and 19% (mixed astigmatism) are corroborated by negative mean magnitudes of error of -0.08 and -0.34 D, and arithmetic mean DVs of 0.38 and 0.65 D for the myopic and mixed astigmatism groups, respectively.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Although they have individually been shown to be safe and effective, there are few comparative studies with other laser platforms [66,67 && ]. Bohac et al [68] prospectively compared outcomes of wavefront-optimized myopic LASIK with the Amaris and the Allegretto and found that the Amaris was more effective in cylinder correction. However, a subsequent vector analysis of astigmatic outcomes by the same group did not reveal any significant difference between platforms [69 & ].…”
Section: Comparison Of Wavefront-optimized Platforms For Laser In-sitmentioning
confidence: 99%
“…Excimer laser-based systems evolved from high energy, low repetition rate lasers that covered a large area of the cornea in a single shot into ∼1000 Hz repetition rate flying spot machines with sophisticated scanning patterns and fast eye tracking systems. [6][7][8][9] Most practical disadvantages of the excimer lasers (intense maintenance required, toxic gases used as gain medium, relatively low stability of output, poor beam quality) have been successfully overcome or at least became manageable by the use of sophisticated engineering solutions and application protocols. 10,11 The clinical outcomes of UV systems for corneal ablation based upon nanosecond solid-state lasers with harmonic generators 12,13 have been demonstrated to be equivalent to those of excimer lasers.…”
Section: Introductionmentioning
confidence: 99%